Pengaruh Kompensasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Pilar Kreasi Mandiri - Arya Fauzy Al askari; Rony Edward Utama (Jurnal Manajemen Dirgantara, 2024)
This study aims to test and analyze the effect of compensation and work discipline on employee performance at PT. Pilar Kreasi Mandiri. The method of data collection in this study was by distributing questionnaires to 50 respondents of PT. Pilar Kreasi Mandiri. The method used is an associative quantitative method using primary data and secondary data. Data analysis techniques used are validity test, reliability test, classical assumption test, determination coefficient analysis (adjusted R2), multiple linear regression analysis, hypothesis testing using SPSS Version 20. The results show that compensation and work discipline have a positive and significant effect on employee performance. Based on the analysis of the determination coefficient, the R Square is 0.861 or 86.1%, while the remaining 13.9% is influenced by other variables that are not studied or observed.